Conflito socioambiental em Baixa Grande, Alcântara – MA: a questão da sustentabilidade e as formas de resistência étnica - Conceição, Moisés do Carmo (2019)
The present work deals with the investigation of a situation of socioenvironmental conflict experienced by social agents and caused by the attempt to install a garbage recycling plant, by the Alcântara Launch Center - CLA, in the quilombola community of Baixa Grande in the municipality of Alcântara – MA. The three types of data collection used in this research were: bibliographic review, direct observation of the community way of life, and individual and collective interviews with social agents. Through the problematization of the ethnic, political, cultural and sociological aspects of this conflict, as well as the questions of the sustainability of the traditional peoples and communities, of the Amazonian territorialities and also the issue of state development policies, aims to understand how does happen the struggle of ethnic resistance of quilombolas as opposed to their antagonists and the impasse in the face of the threat of socio-environmental effects triggered by the attempt to install the plant on a river water source through the Sustenable City of Alcântara Project. Thus, the discourse and counterdiscourse of sustainable development are analyzed for a greater understanding of how, in the name of interests of the "all", the most elementary rights of the quilombolas in Alcântara – MA are superseded.